2020
DOI: 10.1371/journal.pone.0232291
|View full text |Cite
|
Sign up to set email alerts
|

Role of gender in perspectives of discrimination, stigma, and attitudes relative to cervical cancer in rural Sénégal

Abstract: Cervical cancer is the leading cause of female cancer deaths in Sé né gal which is ranked 17 th in incidence globally, however, the screening rate there is very low. Nuanced gendered perceptions and health behaviors of both women and men play a significant role in women's health. Our study analyzed gender differences on perceptions of gender roles, discrimination, cancer attitudes, cancer stigma, and influences in healthcare decision making within our study population to inform ongoing cervical cancer preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…This result was supported by a previous study in England that investigated stigma with the same tools (16). Another study reported the same finding, which showed that people who had a family history of cancer had a positive attitude towards people with cancer (20,21). The consistency among these findings suggested that people will have a lower-level stigma if they have experience in dealing with people with cancer, specifically their family members, and thus they may be more knowledgeable and supportive toward cancer treatment.…”
Section: Discussionsupporting
confidence: 75%
“…This result was supported by a previous study in England that investigated stigma with the same tools (16). Another study reported the same finding, which showed that people who had a family history of cancer had a positive attitude towards people with cancer (20,21). The consistency among these findings suggested that people will have a lower-level stigma if they have experience in dealing with people with cancer, specifically their family members, and thus they may be more knowledgeable and supportive toward cancer treatment.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of high cancer stigma in the studies reviewed range from 26.1% amongst a sample of patients with different types of cancer in Iran Shiri et al [ 64 ] to 35.5% amongst lung cancer patients in the USA [ 37 ]. The included articles showed that the stigma attached to cancer and cancer patients is expressed and experienced from different segments of the society, such as the general public [ 6 , 54 , 56 , 58 , 62 , 63 , 72 ], elites [ 50 ], media and advertising agencies [ 18 , 27 , 55 , 80 ], healthcare providers [ 28 , 34 ]), policy makers [ 49 ] and friends and family members [ 63 , 101].…”
Section: Methodsmentioning
confidence: 99%
“…Some authors attempted to make sense of the reasons behind stigma against cancer and those affected by cancer. Amongst the reasons adduced were: blame apportioning, disgust propensity, gender differences, having not experienced cancer or the behaviours that are thought to cause cancer and being a member of an ethnic minority [ 3 , 6 , 41 , 56 , 62 , 77 ]. The role of gender in cancer stigma is not consistent in literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuanced gendered perceptions and health behaviors of both women and men play a significant role in women's ability to access the care they need. Men or older family members are often the decisionmakers for when and how women may gain access to healthcare (Ongtengco et al, 2020). In the context of early detection of cancer, before doing the IVA test, the wife usually requires permission from her husband.…”
Section: Gender Norms In Family: Applied Ecological Social Modelmentioning
confidence: 99%